'Dreaming Has a Share in History': Biding Time in the Work of Lubaina Himid. Issue 3 (28th June 2021) - Price, Dorothy
Abstract : This essay analyses a selection of work by British painter Lubaina Himid through the lens of time, specifically non‐synchronous time as adumbrated by Ernst Bloch, conjunctural time after Stuart Hall, and constellations of Benjaminian time. It engages in close visual readings of Naming the Money (2004), Tousssaint L'Ouverture (1987), and a series of nine paintings Himid has referred to as the Walter Benjamin Kangas (2016), also known as New Kangas from the Archive . Taking different kinds of time as its structural framework, the essay presents new ways of thinking about these artworks that cross past and present narratives of trauma, political agency, subjectivity and change. The essay demonstrates how the use of colour, installation and collage, in a re‐address to history, to art history, to monuments, to time, to memory and to visibility, are central to Himid's practices as an artist: a practice in which she wrests painting from its traditional function as an instrument for white western canon formation, and re‐deploys it in dialogical relation to its origins.